IMPLEMENTASI MANAJEMEN STRATEGIK DALAM MENINGKATKAN KINERJA GURU PADA SD UNGGULAN IQRO SIGLI - Maulidarni .; Murniati .; Niswanto . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
The implementation of strategic management is able to anticipate the need of improved educational quality in the future. This research aims to find out the strategic formulation, strategic implementation, strategic evaluation, and obstacles found in improving teachers’ performance. The research was conducted by means of qualitative method. The data was collected by doing interview, observation, and documentation. The principal, the vice principal, and the teachers were chosen as the subjects of this research. The results of this research indicated that (1) The strategic formulation in improving the teachers’ performance involved internal and external school components that create several strategic activities in order to improve the teachers’ performance; (2) The strategic implementation in improving the perfomance of the teachers was performed by arranging the school programs which were gradually implemented. They consist of short-term programs, mid-term programs, and long-term programs. Those programs were then implemented gradually and the chances for the suggestions related to the activities were given in the regular meetings; (3) The strategic evaluation in improving the teachers’ performance was conducted twice a semester by means of periodic and continuous monitoring. The result of the evaluation was used as the main principle for the upcoming strategy development; (4) The obstacles of strategic implementation found in improving the teachers’ performance were the lack of facility and infrastructure and the dependency on the center institution that slows down the implementation of the school strategy.Keywords: strategic management and teachers’ performance